2014
DOI: 10.3892/ijo.2014.2725
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2 inhibits TNF-α-induced hepatocellular carcinoma cell metastasis via Erk1/2 downregulation and NF-κB activation

Abstract: Tumor necrosis factor-α-induced protein 8-like 2 (TNFAIP8L2, TIPE2), which belongs to the TNF-α-induced protein 8 family, is a negative regulator of immune homeostasis. Although pro-inflammatory cytokines such as TNF-α have been reported to be involved in liver carcinoma metastasis, the effect of TIPE2 on hepatocellular carcinoma metastasis remains unknown. We demonstrate that TNF-α clearly augments MMP-13/MMP-3 expression and promotes cell migration in HepG2 cells through activation of the Erk1/2-NF-κB pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 39 publications
(54 reference statements)
1
29
0
Order By: Relevance
“…56 It also inhibits the TNFmediated activation of Erk1/2 and NF-κB in an HCC cell line. 68 In contrast, TIPE2 overexpression induced cell death and inhibited Ras-mediated tumorigenesis in mice. 23 In gastric cell lines, increased TIPE2 expression decreased cell proliferation by upregulating N-ras and p27 expression, 53 the latter of which is mediated by interferon regulatory factor 4 via NF-κB; 69 TIPE2 has also been found to regulate AKT and ERK1/2 signaling in these cells 70 as well as GSK3β and downstream β-catenin translocation.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
“…56 It also inhibits the TNFmediated activation of Erk1/2 and NF-κB in an HCC cell line. 68 In contrast, TIPE2 overexpression induced cell death and inhibited Ras-mediated tumorigenesis in mice. 23 In gastric cell lines, increased TIPE2 expression decreased cell proliferation by upregulating N-ras and p27 expression, 53 the latter of which is mediated by interferon regulatory factor 4 via NF-κB; 69 TIPE2 has also been found to regulate AKT and ERK1/2 signaling in these cells 70 as well as GSK3β and downstream β-catenin translocation.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
“…Additionally, a study on HCC showed NF-κB to be involved in TIPE2 mediated lung cancer. TIPE2 suppressed TNF-α induced metastasis of HCC cells via inhibition of NF-κB and ERK1/2 [27]. In addition, TIPE2 also exerted its function through regulation of autophagy, as LC-3B was downregulated in TIPE2 knockout cells.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, adenovirus-mediated human TIPE2 gene transfer (AdVTIPE2) led to the suppression of gastric cancer cells' growth through decreased Akt, ERK1/2, and activation of the intrinsic apoptotic pathway [26]. Besides, TIPE2 suppressed TNF-α-mediated metastasis of hepatocellular carcinoma (HCC) cells by inhibiting nuclear factor kappa B (NF-κB) and Erk1/2, indicating TIPE2 as a plausible target against HCC metastasis [27]. Further, in the case of NSCLC tissues, TIPE2 was found to be upregulated, which exerted a negative correlation with primary tumor size, lymph node metastasis, and advanced clinical stage of the disease [28].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, numerous studies have shown that the TNFAIP8 family is associated with the development of multiple tumors.TNFAIP8 has been demonstrated to be upregulated in NSCLC tumor tissues, gastric adenocarcinoma tissues, platinumresistant epithelial ovarian cancer tissues, and endometrial cancer tissues [10][11][12][13]. TIPE2 expression was more pronounced in colon cancer tissues, but downregulated in HCC [14,15].…”
Section: Discussionmentioning
confidence: 99%